PSYCHOLOGICZNE UWARUNKOWANIA ZACHOWAŃ DZIECI WYRZĄDZAJĄCYCH SZKODĘ A ODPOWIEDZIALNOŚĆ RODZICÓW Z TYTUŁU NADZORU NAD NIMI - Słyk, Jerzy (Zeszyty Prawnicze, 2017)
Psychological Considerations of the Behavior of Children Causing a Damage and Parents’ Liability for Supervision Summary The study concerns the problem of parents’ compensatory liability for a damage caused by their children in a psychological perspective. The author presents basic issues being the subject of the studies on children’s psychology and refers them to the problem of parents’ civil liability for damages caused by their children. First the paper discusses results of the selected researches concerning the relation between the development of a child and his experiences from the early childhood. Then the author introduces scientific typology of so called parental attitudes, parental styles and systems of family upbringing. and afterwards analyses the reasons for children’s aggressive attitudes. The performed analysis enabled the author to draw conclusions related to the application of the law. They concern wide range of liability for child complying not only care but also children’s upbringing.